Polaprezinc reduces paclitaxel-induced peripheral neuropathy in rats without affecting anti-tumor activity - Kuniaki Tsutsumi; Takanori Kaname; Haruka Shiraishi; Takehiro Kawashiri; Nobuaki Egashira (Elsevier, 2016)
Paclitaxel, an anticancer drug, frequently causes painful peripheral neuropathy. In this study, we investigated the preventive effect of polaprezinc on paclitaxel-induced peripheral neuropathy in rats. Polaprezinc (3 mg/kg, p.o., once daily) inhibited the development of mechanical allodynia induced by paclitaxel (4 mg/kg, i.p., on days 1, 3, 5 and 7) and suppressed the paclitaxel-induced increase in macrophage migration in dorsal root ganglion cells. In addition, polaprezinc did not affect the anti-tumor activity of paclitaxel in cultured cell lines or tumor-bearing mice. These results suggest a clinical indication for polaprezinc in the prevention of paclitaxel-induced neuropathy.